Determining the Public Opinion on Rappler as A News Media Critic of the Administration - Conycel Ramirez; Mary Joyce Arroyo; Persephone Castillejos; Princess Marrose Mariano; Cassandra Cristobal (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
With the rise of social media and online platforms wherein information is only just a click away, there is still a grey area as to whether online users trust news sites and pages on the digital space. This study aims to assess and analyze the public perception of Rappler as a news media outlet wherein it highlights its role as a news media critic of the Duterte administration. The researchers collected the needed data to identify the public opinion of Filipino adults who are aged 18 and above regarding Rappler's critical way of reporting. This study is supported by data, articles, and related literature that are mainly focused on media trust, media credibility, and related factors towards the reported trust in media. Moreover, this study expounds the surrounding issues related to Rappler's investigative journalism. The study has been operationalized through online surveys and by setting certain eligibility requirements, which served as the qualifier for the respondents before answering the questionnaire. Additionally, this study shows a glimpse of the Media Effects Theory and its correlation to the study's nature. Upon analyzing the gathered data, results show that most respondents trust Rappler as a news media outlet critical of the Philippine government.